The Implications of the Fourth Industrial Revolution for Information Asymmetry on the Market: Selected Aspects - Płonka, Maria (Journal of Public Governance, 2021)
Objectives: The identification and systematisation of the phenomenon of information asymmetry on the market in theory and practice, and anticipating the impact of this phenomenon on the market and socio-economic relations in the era of the Fourth Industrial Revolution.Research Design & Methods: Theoretical and cognitive studies, case studies, and inductive reasoning.Findings: In the era of the Fourth Industrial Revolution, the innovation and information sector determines changes in the direction, dynamics, and structure of socio-economic development, which means that information has become an independent resource of special value. In the face of changes, the asymmetry of information on the market will deepen. This is due to the growing gap between the exponential increase in knowledge and anti-knowledge, and the limited, constant perception of the human brain and human tendency to opportunism, which means that in the field of information processing, artificial intelligence will be winning against human intelligence. Against this background, new threats are emerging that require new knowledge, skills, and competences from market participants and the state.Implications / Recommendations: Solving the problem of information asymmetry is a common economic good that should be co-created by all sides of social, market, and public relations through regulatory and educational mechanisms. It is better to anticipate the cooperation of human intelligence with that of machines rather than engage in a conflict. The use of rich information resources, including the selection of irrelevant, manipulated, or false information will become a key skill of market participants, and the state should, through its tools, eliminate the negative effects of information asymmetry.Contribution / Value Added: The subjective evolution of approaches to the phenomenon of information asymmetry from classical economics to behavioural economics, the identification of the relationship between information asymmetry and moral hazard and their consequences, the exemplification of problems on the basis of positive economics in the conditions of the Fourth Industrial Revolution.Article classification: theoretical and review articleJEL classification: D82, D91, D81, B25, D01